1987
DOI: 10.1021/ma00174a011
|View full text |Cite
|
Sign up to set email alerts
|

Pulse radiolysis study on organopolysilane radical anions

Abstract: Poly(methylpropylsilane) (PMPrS) and poly(methylphenylsilane) (PMPS) were investigated by pulse radiolysis with 2-ns time resolution. PMPrS and PMPS solutions in tetrahydrofuran (THF) exhibit strong single absorption bands at 363 and 372 nm, respectively, in the transient spectra. These transient species react with pyrene to produce pyrene radical anions. They also decay in reaction with added CHC1S. Chloromethylated PMPS does not exhibit such a transient absorption, indicating that electron dissociative attac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
40
0

Year Published

1990
1990
2015
2015

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 74 publications
(41 citation statements)
references
References 1 publication
1
40
0
Order By: Relevance
“…This is indicative that one can easily estimate the conformation of the -conjugated polymers in solvent at any temperatures by the simple spectroscopy of -conjugated polymer solutions. Despite positive charge being the dominant charge carriers in the transport process, there have been few dynamics or quantitative analyses on the electronic state of positive charges on the Si or Ge chain other than by transient spectroscopy 12,13 or electron spin resonance. 14,15 Localization of the charge carriers was revealed to be suppressed in the -conjugated polymers bearing bulky pendant groups, suggesting not only that the localization in typical dialkyl substituted polymers arises from the flexibility of Si(Ge) catenation, but also that delocalization occurs in -conjugated polymers with stiff or rod-like skeletons.…”
Section: -4mentioning
confidence: 99%
See 1 more Smart Citation
“…This is indicative that one can easily estimate the conformation of the -conjugated polymers in solvent at any temperatures by the simple spectroscopy of -conjugated polymer solutions. Despite positive charge being the dominant charge carriers in the transport process, there have been few dynamics or quantitative analyses on the electronic state of positive charges on the Si or Ge chain other than by transient spectroscopy 12,13 or electron spin resonance. 14,15 Localization of the charge carriers was revealed to be suppressed in the -conjugated polymers bearing bulky pendant groups, suggesting not only that the localization in typical dialkyl substituted polymers arises from the flexibility of Si(Ge) catenation, but also that delocalization occurs in -conjugated polymers with stiff or rod-like skeletons.…”
Section: -4mentioning
confidence: 99%
“…12 Figure 4 shows a series of transient absorption spectra of anion radicals observed in PH1-12 as the examples of the transient absorption spectra. The spectra observed for anion radicals of MEn and PDn are almost identical, with only a small dependence on the chain length of n-alkyl substituents.…”
mentioning
confidence: 99%
“…The electronic absorption spectroscopy is convenient technique to determine the electronic excited states of polysilanes. Transient absorption spectra of polysilanes in organic solvents after electron beam irradiation show that the radical ions (cation and anion) of polysilanes have a strong absorption band at UV region [11,12]. This band is assigned to an electronic transition of unpaired electron on Si-Si skeleton.…”
Section: Introductionmentioning
confidence: 99%
“…The permethyl-oligosilane Si n (CH 3 ) 2n+2 (n = [8][9][10][11][12][13][14][15][16][17][18][19][20] was chosen as a model of polysilane. We showed that excess electron and hole are fully delocalized along the skeleton of linear polysilane.…”
Section: Introductionmentioning
confidence: 99%
“…So far the radical anions of poly(methyl methacrylate) (PMMA) [46,47], substituted PMMA [46,47], poly(4-vinylbiphenyl) (PVB) [47-50], poly(1-vinylpyrene) (PVP) [50], organopolysilane [51] and substituted polyacetylene [52] have been studied. Subsequent electron attachment to solute polymers leads to the formation of polymer anions.…”
Section: Polymer Ions In Solutionmentioning
confidence: 99%